2002
DOI: 10.1177/1073191102009001008
|View full text |Cite
|
Sign up to set email alerts
|

Identifying faking bad on the Minnesota Multiphasic Personality Inventory—Adolescent with Mexican Adolescents

Abstract: This study examined the extent to which the validity scales of the Minnesota Multiphasic Personality Inventory-Adolescent identified Mexican adolescents who were instructed to fake bad. Validity scales data were used to differentiate between nonclinical adolescents instructed to fake bad and both clinical and nonclinical adolescents who received standard instructions. Participants were 59 male and 87 female Mexican high school students and 59 male and 87 female Mexican adolescents from clinical settings. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…These studies have generally indicated that the traditional validity scales appear to operate in other languages and cultures as they do in the United States. For example, in Italy, Sirigatti and Giannini (2000) replicated the findings of developmental research on the S scale in the United States; in Korea, Hahn (2001) cross-validated the effectiveness of the MMPI-2 validity scales at assessing fake good and fake bad responding; in Mexico, Lucio, Duran, Graham, and Ben-Porath (2002) examined the performance of the traditional validity scales with adolescents; and in Puerto Rico, Jana (2001) studied the MMPI validity scales in detecting malingered psychiatric disorders . In addition, research has been devoted to adapting MMPI-2 validity scales to Chinese populations, for example, the F scale and the K scale (Gao, 2001;Ji et al, 1999;Zhang, 1992).…”
Section: Assessment Of Invalid Response Patternsmentioning
confidence: 94%
“…These studies have generally indicated that the traditional validity scales appear to operate in other languages and cultures as they do in the United States. For example, in Italy, Sirigatti and Giannini (2000) replicated the findings of developmental research on the S scale in the United States; in Korea, Hahn (2001) cross-validated the effectiveness of the MMPI-2 validity scales at assessing fake good and fake bad responding; in Mexico, Lucio, Duran, Graham, and Ben-Porath (2002) examined the performance of the traditional validity scales with adolescents; and in Puerto Rico, Jana (2001) studied the MMPI validity scales in detecting malingered psychiatric disorders . In addition, research has been devoted to adapting MMPI-2 validity scales to Chinese populations, for example, the F scale and the K scale (Gao, 2001;Ji et al, 1999;Zhang, 1992).…”
Section: Assessment Of Invalid Response Patternsmentioning
confidence: 94%
“…The WASI is not a validity test and a search on Google Scholar found no studies that assessed its ability to detect negative response bias 6 . The MMPI‐A has a much smaller literature on negative response bias than the adult versions, and while positive findings have been reported for detecting generalized feigning (Bagdade, 2003; Lucio et al., 2002; Stein et al., 1995; but see Rogers et al., 1996), no studies examined its ability to detect feigned memory problems or CSA. The MMPI‐A lacks the recently added validity scales (FBS/Symptom Validity Scale, RBS, Fs) on the adult versions that appear more sensitive to feigned cognitive symptoms than the F scale (Aparcero et al., 2022), and only two questions (# 161 and 214) on the entire test inquire about memory.…”
Section: Critique Of Acklin's Assessment For Negative Response Biasmentioning
confidence: 99%
“…No obstante, se ha cuestionado el empleo del MMPI como instrumento válido y fiable para valorar la simulación (Arce, Pampillón & Fariña, 2002;González & Iruarrizaga, 2006;Inda, Lemos, López et al, 2006) y el empleo de muestras de análogos (Lucio, Duran, Grahm et al, 2002;Medoff, 1999). De ahí que se hayan desarrollado pruebas para evaluar la simulación unicamente en adultos, (Rogers, 1984b;Rogers, 1997;Rogers, Gillis & Bagby, 1990;Rogers, Gillis, Dickens et al, 1991;Rogers, Jackson, Sewell et al, 2005;Rogers, Kropp, Bagby et al, 1992;Schretlen, 1986;Smith, Borum & Schinka, 1993;Smith & Burger, 1997).…”
Section: Introductionunclassified